2002
DOI: 10.1080/08039480252803864
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of the reformation of psychiatric care: A 15-year follow-up study

Abstract: Although there are a great many epidemiological studies of psychiatric diseases and the outcomes of controlled rehabilitation programmes, there is a shortage of studies of routine psychiatric care. This study is a retrospective cohort study of the total number (n=138) of patients receiving inpatient care at a psychiatric rehabilitation clinic in Jönköping during 1984. The follow-up period is 15 years, 1984-98. The group had a considerable amount of inpatient care, but this decreased dramatically during the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The mortality gap for death from unnatural causes between all eligible patients and the general population decreased apparently over the three periods of reform ( Table 5 ). Our results are supported by the findings of a previous study of specific populations that received mental health care during the reform of psychiatric services (Bulow, Svensson, & Hansson, 2002 ; Farragher, Carey, & Owens, 1996 ; Pirkola et al, 2007 ). However, some previous studies showed a persistent excessive mortality due to unnatural causes during the periods of deinstitutionalization (D'Avanzo et al, 2003 ; Rasanen et al, 2003 ).…”
Section: Discussionsupporting
confidence: 91%
“…The mortality gap for death from unnatural causes between all eligible patients and the general population decreased apparently over the three periods of reform ( Table 5 ). Our results are supported by the findings of a previous study of specific populations that received mental health care during the reform of psychiatric services (Bulow, Svensson, & Hansson, 2002 ; Farragher, Carey, & Owens, 1996 ; Pirkola et al, 2007 ). However, some previous studies showed a persistent excessive mortality due to unnatural causes during the periods of deinstitutionalization (D'Avanzo et al, 2003 ; Rasanen et al, 2003 ).…”
Section: Discussionsupporting
confidence: 91%
“…How people with mental health problems experience life in the community has been studied from different perspectives, and investigated by quantitative as well as qualitative research methods. Some recurrent findings from quantitative studies reveal unmet needs for social contact, relationships and activities (Bulow, Svensson, and Hansson 2002;Hansson et al 2003;Jansson, Sonnander, and Wiesel 2003) and the importance of such factors for self-reported 'quality of life' (Borge et al 1999;Elstad 1999;Oliver, Huxley, and Bridges 1996). Qualitative studies have reported feelings of loneliness, shame and psychological pain, fear of neglect and exclusion, passivity and needs for support but not wanting to be subjected to control (Birkeland and Kristoffersen 2004;Erdner et al 2002;Granerud and Severinsson 2006;Green et al 2002).…”
Section: Previous Researchmentioning
confidence: 99%
“…The number of psychiatric beds in Sweden has been reduced and lengths of stay have been shortened [13,14]. Psychiatric hospital beds have to be used as effective as possible in order to help patients in acute phases of mental illness being able to rely on outpatient services in the community.…”
Section: Discussionmentioning
confidence: 99%